Surgical Treatment of Osteopetrosis-Related Femoral Fractures: Two Case Reports and Literature Review - Ahmet Aslan; Yakup Barbaros Baykal; Emin Uysal; Tolga Atay; Vecihi Kirdemir; Metin Lütfi Baydar; Nevres Hürriyet Aydoğan (Case Reports in Orthopedics)
Osteopetrosis is a rare hereditary disease which is characterized by increased bone density. Bone resorption is insufficient or fails due to the osteoclast defect in osteopetrosis. Half of the patients are asymptomatic and diagnosed incidentally or based on the presence of fracture. Adult onset osteopetrosis usually presents with hip and proximal femoral fractures. Internal fixation can be performed; however, technical challenges may be experienced due to increased bone density. As in other fractures, nonunion or varus malunion of these fractures may occur. Although rare, osteopetrosis may complicate treatment of fractures in such patients. In this study, we aimed to present two new cases of ADO type II with an osteopetrotic femoral fracture along with the clinical and radiological findings in the light of a comprehensive literature review. Orthopaedics surgeons should be aware of intraoperative technical difficulties and possible postoperative complications during the follow-up period. Investigation would be beneficial for the diagnosis of osteopetrosis such the patient with fractures who has minor trauma history and increased bone density in radiography.